BASIC PHYSICAL QUALITIES IN WRESTLING AND METHODS OF THEIR DEVELOPMENT - Soliha, Bekzodova (Research Focus International Scientific Journal, 2026)
This work examines the development of key physical qualities important in wrestling, such as strength, speed, endurance, agility, and flexibility. It briefly analyzes the main training methods used to develop and improve these qualities, as well as their impact on sports performance. The study includes recommendations aimed at improving the physical fitness of wrestlers.